Gravitação em branas com espessura: testes observacionais e alguns efeitos - Silva, Alex de Albuquerque (2014)
Theories of extra dimensions have been extensively studied in recent years with the original intention of solving the hierarchy problem. Among the models of extra dimensions we can mention the braneworld models, more precisely, the Randall-Sundrum model, which considers our universe as a brane embedded in an ambient space with an extra dimension of infinite size. The fundamental aspect of the brane models is that matter and fields are confined in a hypersurface and only gravity has access to all dimensions. Thus, observational tests involving gravity may provide a way of verifying the existence of extra dimensions. With this idea in mind, in this work, we find black hole solutions in a regularized version of a RSII type brane and then we consider two classical tests of general relativity to these solutions. We studied the in uence of transversal movement in the four-dimensional path of the particles. We note that the de ection of light and the time delay, in this scenario, depend on the energy ( frequency ) of the light signal and can, therefore, give rise to the phenomenon of gravitational rainbow. We also discuss a model of thick branes known as the split fermion model. In this model electrons and protons are located on di¤erent hypersurfaces of the brane. We found that, in the presence of a gravitational eld generated by a massive body, these particles will experience di¤erent four-dimensional geometries. This violation of the equivalence principle, from the viewpoint of four-dimensional observers, produces interesting phenomena as, for instance, the gravitational induction of an electric dipole in a hydrogen atom. We veri ed that the Hamiltonian that describes this e¤ect has the same form of the Stark Hamiltonian, i.e., H = ~A ~r, where the tidal acceleration ~A(due to the separation of electron and proton in the extra dimension) substitutes the electric eld and the reduced mass atom replaces the electric charge.